Building trauma capability: using geospatial analysis to consider military treatment facilities for trauma center development - Stacy A Shackelford; Matthew D Tadlock; Blair C Lee; Christian S McEvoy; Dan Ross-Li; Emily A Norris; Shane D Jensen (Trauma Surgery & Acute Care Open)
Background The Military Health System must develop and sustain experienced surgical trauma teams while facing decreased surgical volumes both during and between deployments. Military trauma resources may enhance local trauma systems by accepting civilian patients for care at military treatment facilities (MTFs). Some MTFs may be able to augment their regional trauma systems by developing trauma center (TC) capabilities. The aim of this study was to evaluate the geographical proximity of MTFs to the continental US (CONUS) population and relative to existing civilian adult TCs, and then to determine which MTFs might benefit most from TC development.Methods Publicly available data were used to develop a list of CONUS adult civilian level 1 and level 2 TCs and also to generate a list of CONUS MTFs. Census data were used to estimate adult population densities across zip codes. Distances were calculated between zip codes and civilian TCs and MTFs. The affected population sizes and reductions in distance were tabulated for every zip code that was found to be closer to an MTF than an existing TC.Results 562 civilian adult level 1 and level 2 TCs and 33 military medical centers and hospitals were identified. Compared with their closest civilian TCs, MTFs showed mean reductions in distance ranging from 0 to 30 miles, affecting populations ranging from 12 000 to over 900 000 adults. Seven MTFs were identified that would offer clinically significant reductions in distance to relatively large population centers.Discussion Some MTFs may offer decreased transit times and improved care to large adult populations within their regional trauma systems by developing level 1 or level 2 TC capabilities. The results of this study provide recommendations to focus further study on seven MTFs to identify those that merit further development and integration with their local trauma systems.Level of evidence IV.